Performa Pertumbuhan Benih Ikan Nila (Oreochromis niloticus) Melalui Penambahan Enzim Papain - Veronitta Hodifa; Retno Cahya Mukti (University of Prof. Dr. Hazairin, SH, 2023)
As a maritime country, Indonesia relies heavily on the aquaculture sector, including freshwater aquaculture. Freshwater aquaculture has been widely practised in the aquaculture of nila tilapia fish (Oreochromis niloticus). The obstacle that often arises in nila tilapia fish culture is the low growth of fish. Factors that cause low fish growth are the low ability of fish to digest the feed given. The papain enzyme can be used as a protein catalyst in feed, increasing growth rates and reducing production costs. This study was conducted from November to December 2022 at the Seberang Ulu 1 District, Palembang, South Sumatra. This study used an experimental method with treatment P0 being the control (without adding the papain enzyme) and P1 being the treatment with adding the papain enzyme at a dose of 2.25%. The P1 treatment produced the highest results: the absolute length growth of 3.49 cm, the absolute weight of tilapia of 9.8 g, feed efficiency of 98.30% and survival of 88.80%.